2010
DOI: 10.1590/s1519-69842010005000014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4-D on the germination of megaspores and initial development of Regnellidium diphyllum Lindman (Monilophyta, Marsileaceae)

Abstract: Regnellidium diphyllum is considered as endangered, occurring in the State of Rio Grande do Sul, Brazil, and a few adjoining localities in Uruguay, Argentina and the State of Santa Catarina. It grows in wetlands frequently altered for agricultural activities. Herbicides based on 2,4-dichlorophenoxyacetic acid (2,4-D) are widely used in these fields. The effects of 2,4-D on the germination of megaspores and initial sporophytic development of R. diphyllum were in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Assim, alguns fatores não considerados neste estudo podem estar influenciando a comunidade de samambaias no sítio, como o spray dos agrotóxicos lançados nas plantações de hortaliças da área lindeira e que, por ação do vento, podem estar sendo carregados ao interior do fragmento, acarretando decrés-cimo das espécies de samambaias epifíticas e de sua cobertura. Em estudo desenvolvido por Cassanego et al (2010), levando em conta a ação de metais pesados encontrados em herbicidas sobre a germinação de megásporos e desenvolvimento esporofítico inicial de Regnellidium diphyllum Lindm., constatou-se o efeito deletério tanto na germinação quanto no desenvolvimento inicial dessa samambaia. Becker et al (2015) verificaram menor diversidade de espécies epifíticas, incluindo samambaias em ambientes com mais concentração de metais pesados.…”
Section: Os Resultados Sustentam Que O Interior Do Macacounclassified
“…Assim, alguns fatores não considerados neste estudo podem estar influenciando a comunidade de samambaias no sítio, como o spray dos agrotóxicos lançados nas plantações de hortaliças da área lindeira e que, por ação do vento, podem estar sendo carregados ao interior do fragmento, acarretando decrés-cimo das espécies de samambaias epifíticas e de sua cobertura. Em estudo desenvolvido por Cassanego et al (2010), levando em conta a ação de metais pesados encontrados em herbicidas sobre a germinação de megásporos e desenvolvimento esporofítico inicial de Regnellidium diphyllum Lindm., constatou-se o efeito deletério tanto na germinação quanto no desenvolvimento inicial dessa samambaia. Becker et al (2015) verificaram menor diversidade de espécies epifíticas, incluindo samambaias em ambientes com mais concentração de metais pesados.…”
Section: Os Resultados Sustentam Que O Interior Do Macacounclassified
“…The species grows in wetlands, the leaf lamina frequently floating and the rhizome developing in the humid soil or mud. Previous studies reported effects of heavy metals and other pollutants on the early development of R. diphyllum (Wunder et al, 2009;Cassanego et al, 2010;Droste et al, 2010;Kieling-Rubio et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro culture methods provide controlled conditions for propagating sporophytes and studying fern biology, since germination and growth requirements of the Neotropical species are poorly understood (Fernández et al, 1999;Cassanego et al, 2010).…”
Section: Introductionmentioning
confidence: 99%